Kajian Kuantitas dan Kualitas Taman Aktif di Kecamatan Tembalang dan Kecamatan Banyumanik - Intan Budiarti; Retno Susanti (Jurusan Perencanaan Wilayah dan Kota, 2020)
Tembalang District and Banyumanik District are districts that have several well-known universities with population growth more rapidly than other districts in Semarang City. This increase in population can also trigger an increase in development to meet housing needs. This increase in development often forgets that active parks must be provided to maintain a balance between built up and non-built lands. The purpose of this study was to examine the quantity and quality of active parks in Tembalang District and Banyumanik District. The method used in this research is quantitative as well as qualitative research methods or commonly known as mixed research methods. Quantitative research uses descriptive normative analysis methods, while qualitative research uses content analysis methods. Based on the objectives to be achieved in this study, the results are obtained that the quantity of active parks that still do not meet the needs of residents in Tembalang District and Banyumanik District. This is indicated by the area of the park that still needs to be provided in Tembalang District is 32,559 m2 and Banyumanik District is 21,005 m2. As for the assessment of the quality of existing active parks, it has been well proven by the opinion of respondents who said that the condition of the sports field, parking, park chairs, safety, and cleanliness of the park was good. As for the quality that is considered poor, only children's play facilities, lighting, and the availability of vegetation.